Downstream development strategy of processing industry in Jambi Province - Erni Achmad; M. Rachmad R.; Zamzami Zamzami; Arman Delis (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
The food and beverage industry, the paper and paper goods industry, and the rubber industry, rubber and plastic goods are leading industries that play an important role in the regional economy of Jambi Province. Therefore, policies are needed to sustain leading industries' growth and development. This research aims to formulate a downstream strategy for the leading processing industry in Jambi province. The method used is the Analytical Network Process (ANP). The analysis results show that the priority strategy in the downstream development of the three leading industries in Jambi Province is optimizing the government's role in policy and funding for the downstream program.